Correlation between Speeches of the President of Lithuania and the National Day Celebrations in the period 1920-1938: influential Communication - Vita Ulytė-Grigelevičienė (Lietuvos Istorijos Studijos)
The present article discusses distinctive aspects of the National Day (Tautos šventė) celebrations, which were aimed at the general public, in Lithuania in the period between 1920 and 1938 and the form and content of the speeches delivered by the President of State during these celebrations in order to make a strategic impact on the citizens. With the aim of examining the character of these phenomena, the research focuses on the aspect of influential communication. The research presented in the article has been carried out using the methods of statistical/contrastive analysis and rhetorical analysis. The analysis of the subject starts with a brief overview of the origins and process of the National Day in Lithuania and the examination of its distinctive aspects. The objective of this part of the analysis is to determine the main reason for the existence of the National Day in Lithuania. The article further examines the reaction of the National Day celebration participants to the public appearance of the President of State and explores the features of the impact strategy revealed by the President's opening speech made on the occasion of the celebration. The research aims at reconstructing the overall pattern of influential communication, which was reflected in the connection between the President of State and the crowds of general public at that time.